Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1111/j.1365-2826.2007.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Caloric Intake on a Fat‐Rich Diet: Role of Ovarian Steroids and Galanin in the Medial Preoptic and Paraventricular Nuclei and Anterior Pituitary of Female Rats

Abstract: Previous studies in male rats have demonstrated that the orexigenic peptide galanin (GAL), in neurones of the anterior parvocellular region of the paraventricular nucleus (aPVN) projecting to the median eminence (ME), is stimulated by consumption of a high-fat diet and may have a role in the hyperphagia induced by fat. In addition to confirming this relationship in female rats and distinguishing the aPVN-ME from other hypothalamic areas, the present study identified two additional extra-hypothalamic sites wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 86 publications
7
32
0
Order By: Relevance
“…Estrogen is known to potentiate corticosterone levels (Kitay et al 1965) and protect against high fat diet-induced insulin resistance and glucose intolerance (Riant et al 2009). Plasma estrogen levels were not evaluated in our study, but it is known to increase proportionally with the fat content of diet in adult female rats (Leibowitz et al 2007). Consequently, an increase of estradiol levels in adolescent HF females could have facilitated the elevation of corticosterone levels observed after puberty.…”
Section: Discussionmentioning
confidence: 98%
“…Estrogen is known to potentiate corticosterone levels (Kitay et al 1965) and protect against high fat diet-induced insulin resistance and glucose intolerance (Riant et al 2009). Plasma estrogen levels were not evaluated in our study, but it is known to increase proportionally with the fat content of diet in adult female rats (Leibowitz et al 2007). Consequently, an increase of estradiol levels in adolescent HF females could have facilitated the elevation of corticosterone levels observed after puberty.…”
Section: Discussionmentioning
confidence: 98%
“…1) (92). This system regulates several functions of the gastrointestinal tract, such as motility, secretion, absorption, microcirculation of the gut, local immune defence and cell proliferation (96)(97)(98)(99)(100)(101)(102)(103)(104)(105). This regulatory system consists of a large number of bioactive messengers (Table I).…”
Section: The Neuroendocrine System (Nes) Of the Gutmentioning
confidence: 99%
“…In rats, galanin was also reported to increase preference for a high-fat diet given a choice between fat, carbohydrate, and protein (Tempel et al, 1988), although other contemporary studies observed less of a difference in macronutrient choice Crawley, 1999;see Gundlach, 2002, for review). More recent studies in female rats also documented that ovarian steroids likely function together with galanin in a neural circuit, involving the medial preoptic nucleus, the anterior PVN, and the median eminence and anterior pituitary, to coordinate feeding behavior with reproductive function to promote consumption of a fatrich diet at times of increased energy demand (Leibowitz et al, 2007). Kyrkouli and colleagues (2006) further examined the influence of PVN galanin on dark/active phase nutrient intake in rats in a self-selection feeding paradigma choice between isocaloric diets enriched in protein, carbohydrate, or fat.…”
Section: A Feeding and Energy Homeostasismentioning
confidence: 99%